Bismuth Ferrite Enhanced ZnO Solid State Dye-sensitised Solar Cell. (2016) - Loh, Leonard; Briscoe, Joe; Dunn, Steve
Abstract: ZnO dye sensitized solar cells have been reported to be plagued with issues of dye aggregation which increased current recombination. This dye aggregation has been linked to the pH 5 ruthenium-based dye solutions, which is below ZnO's point of zero charge of pH 9, resulting in positive surface charges on ZnO which form Zn2+ - dye complexes. In this paper, a heterogeneous architecture of ZnO and bismuth ferrite (BiFeO3 or BFO) is synthesized using a technique which allows the synthesis using purely chemical solution techniques. BFO is a perovskite studied extensively for its multiferroic properties and its potential for anomalous photovoltages. The solid state solar cells are sensitized with N719, and uses copper thiocyanate (CuSCN) as a hole conductor. The ZnO-BFO-N719-CuSCN heterogeneous architecture solar cell showed efficiencies which increased ca four-fold to 0.38% and Jsc which doubled to 1.38 mA/cm2 compared to ZnO-N719-CuSCN architectures. We will report that the addition of BFO improved performances due to the reduction of dye aggregation due to BFO's pzc of pH 6.5 which is close to the pH 5 of the dye solution, as well as BFO's role as an electron blocking layer which prevents the back tunneling of electrons from ZnO to CuSCN.